Delirium Induced by Quetiapine and the Potential Role of Norquetiapine - Almeida, Filipe; Albuquerque, Elisabete; Murta, Ilda (Frontiers in Neuroscience, 2019)
Quetiapine in an atypical antipsychotic used frequently for delirium and behavioral and psychological symptoms in dementia. However, its potential anticholinergic effects, mediated primarily through its metabolite norquetiapine, could present as counterproductive adverse effects in these situations. There is little data published discussing this potential negative impact on quetiapine’s safety and tolerability, especially in the elderly. Here, we present what is, to our knowledge, the first published case report of delirium induced by low-dose quetiapine, in a 95-year-old patient with no prior history of mental illness, and the potential role of its metabolite norquetiapine.